Bis(perchlorato-κO)tetrakis[1-(2-pyridyl)-4-(4-pyridylmethyl-κN)piperazine]cadmium(II) (Acta Crystallographica Section E, 2009)
In the title compound, [Cd(ClO4)2(C15H18N4)4], the CdII ion is coordinated in a slightly distorted octahedral environment by two trans monodentate perchlorate ligands and four 1-(2-pyridyl)-4-(4-pyridylmethyl)piperazine (pmpp) ligands. In the crystal structure, molecules are organized into layers parallel to the ab plane by C—H...O interactions. Similar interactions promote the stacking of these layers into the three-dimensional crystal structure.